Copper-catalyzed aminooxygenation of styrenes with N-fluorobenzenesulfonimide and N-hydroxyphthalimide derivatives - Li, Yan; Zhou, Xue; Zheng, Guangfan; Zhang, Qian (Beilstein Journal of Organic Chemistry, 2015)
A copper-catalyzed aminooxygenation reaction of styrenes with N-fluorobenzenesulfonimide and N-hydroxyphthalimide derivatives has been developed. The aminooxygenation product could be converted into the corresponding alcohol or free amine through the cleavage of the N–O or C–N bond of the N-hydroxyphthalimide moiety.
Keywords: aminooxygenation of styrenes; copper catalysts; N-fluorobenzenesulfonimide; N-hydroxyphthalimide derivatives